Functional acrylate, preparation method and application thereof

CN117756686BActive Publication Date: 2026-10-20DINGYUAN YUNSEN TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311737642.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2026-10-20
Estimated Expiration
2043-12-18

AI Technical Summary

Technical Problem

酚的甲基衍生物不仅致畸,而且致癌

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117756686B_ABST
    Figure CN117756686B_ABST
Patent Text Reader

Abstract

The application discloses a functional acrylate, a preparation method and application thereof. The application adopts a reaction of fluorine-containing alkylthio propionic acid and hydroxyalkyl acrylamide / acrylate under the condition of a catalyst to prepare acrylate monomer with a thioether group. Through synergistic action of C-F bond and thioether bond, the material has more excellent anti-aging performance. The synthesis method is simple, safe and beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fine chemicals, specifically relating to a functional acrylate, its preparation method, and its application. Technical Background

[0002] After sunlight is filtered by the atmosphere, the wavelength range of light reaching the ground is mainly between 290 and 3000 nm. Of this, less than 5% is ultraviolet light in the 290 nm to 400 nm range, but this small amount of ultraviolet light is the main cause of polymer aging. Because the bond energies of the main chemical bonds in polymers correspond to a portion of the wavelength energy in ultraviolet light, polymer materials can absorb this ultraviolet light, leading to the breakage of chemical bonds and further causing the material to age and degrade.

[0003] The covalent bond energy of fluorine (F) is relatively high, close to the highest energy level in ultraviolet light. Therefore, the likelihood of breaking the CF bond within the visible-ultraviolet range is low. The CF covalent bond can resist 90% of ultraviolet radiation. The thioether group can absorb ultraviolet light in the wavelength range of 200-400 nm, which is precisely the most dangerous ultraviolet wavelength range in solar radiation.

[0004] Patent CN101693662B discloses a method for synthesizing such bisphenol monoacrylates. The method involves first synthesizing an intermediate antioxidant, methylenebis(4-methyl-6-tert-butylphenol), using 2-tert-butyl-p-cresol, an aqueous formaldehyde solution, and an emulsifier. The intermediate antioxidant is then added to a reaction vessel, and the water in the system is separated by reflux with toluene. Next, acrylic acid, triethylamine, and phosphorus oxychloride are added, and the mixture is refluxed for 4 hours. After washing and separation, the mixture is filtered and centrifuged to obtain the crude product. This method generates a large amount of aldehyde-containing wastewater in the first step and uses the hazardous chemical phosphorus oxychloride in the second step, both of which pose hazards to human health and the environment.

[0005] Patent CN202010599527.6 discloses a layered bisphenol acrylate antioxidant and its preparation method. The method involves reacting bisphenol hydroxyl groups [2,2] with cycloaramine and acrylic anhydride under alkaline catalytic conditions to obtain a bisphenol acrylate antioxidant with a cycloaramine structure. Through the transcyclic conjugation effect of [2,2] with the cycloaramine, the synergistic effect of the phenolic hydroxyl group and the phenolic acrylate is increased, resulting in superior anti-aging properties.

[0006] All of the above schemes use phenolic substances as the main raw materials. Phenolic compounds are highly toxic organic pollutants. They are widely present in industries such as petrochemicals, printing and dyeing, and pesticides. The presence of phenolic substances in industrial wastewater makes surface water extremely susceptible to pollution. Methyl derivatives of phenols are not only teratogenic but also carcinogenic. Their toxicity increases with the degree of substitution on the aromatic ring.

[0007] Phenolic compounds can enter the human body through the digestive tract, respiratory tract, and skin, binding to proteins in cell protoplasm and causing cell inactivation. In severe cases, they can cause spinal cord irritation, leading to systemic poisoning. Therefore, it is necessary to invent an acrylic monomer that is free of phenolic substances, safe, environmentally friendly, and has antioxidant properties. Summary of the Invention

[0008] To address the shortcomings of the existing technologies, this invention provides a safe and environmentally friendly functional acrylate free of phenolic substances, along with its preparation method and applications. This invention utilizes a fluoroalkylthiopropionic acid reacting with hydroxyalkylacrylamide / acrylate under catalytic conditions to prepare an acrylate product with thioether groups. Through the synergistic effect of the CF bond and the thioether bond, the substance exhibits superior anti-aging properties. The synthesis method of this invention is simple, safe, and conducive to industrial production.

[0009] The functional acrylate of this invention has the following structural formula:

[0010] Rf-CH2CH2-S-CH2CH2COOR1XCOCR2=CH2;

[0011] Where Rf = F(CF2) n -, n=4~6; R1=-(CH2) m -, m=1~3; R2=-H, -CH3, -F or -Cl; X=NH or O.

[0012] Furthermore, Rf = F(CF2) n -, n=6, that is, Rf=-C6F 13 R1 = -(CH2) m -, m=2, i.e. -(CH2CH2)-; R2=-H.

[0013] The method for preparing functional acrylates of the present invention involves reacting fluoroalkylthiopropionic acid with N-hydroxyacrylamide or hydroxyalkyl acrylate as raw materials in the presence of a solvent, a catalyst, and a polymerization inhibitor.

[0014] The molar ratio of the fluoroalkylthiopropionic acid to N-hydroxyacrylamide or hydroxyalkyl acrylate is 1:1 to 1.5, preferably 1:1.1 to 1.2.

[0015] The solvent is selected from toluene, n-hexane, and cyclohexane, with cyclohexane being preferred. The amount of solvent added is 0.2 to 1.2 of the total mass of the reactants (i.e., the total mass of fluoroalkylthiopropionic acid and N-hydroxyacrylamide or hydroxyalkyl acrylate, the same below), preferably 0.5 to 0.7.

[0016] The catalyst is selected from p-toluenesulfonic acid, sulfuric acid, and sodium bisulfate, with p-toluenesulfonic acid being preferred. The amount of catalyst added is 0.2-2% of the total mass of the reactants, preferably 0.6-0.8%.

[0017] The polymerization inhibitor is selected from hydroquinone, 4-methoxyphenol, and 4-hydroxy-TEMPO, with 4-methoxyphenol being preferred. The amount of the polymerization inhibitor added is 0.05% to 0.5% of the total mass of the reactants, preferably 0.1% to 0.25%.

[0018] In the preparation of functional acrylates, the reaction temperature is 70–150℃, preferably 80–120℃; the reaction time is 8–30 hours, preferably 12–20 hours.

[0019] The reaction route is shown below:

[0020] Rf-CH2CH2-S-CH2CH2COOH+CH2=CR2COXR1OH→Rf-CH2CH2-S-CH2CH2COOR1XOCCR2=CH2

[0021] The fluorinated alkylthiopropionic acid is prepared by reacting tridecafluorooctyl mercaptan with acrylic acid, and the reaction route is shown below:

[0022] C6F 13 -CH2CH2-SH+CH2=CHCOOH→C6F 13 -CH2CH2-S-CH2CH2COOH

[0023] Specifically, the reaction involves an addition reaction of tridecafluorooctyl mercaptan and acrylic acid under alkaline conditions. The alkaline substance used is triethylamine, triethanolamine, etc. The reaction temperature is 30–60°C, and the reaction time is 12–18 hours.

[0024] For example, a 1000ml four-necked glass bottle was equipped with a magnetic stirrer, thermometer, spiked column, collecting bottle and condenser, and constant-pressure dropping funnel. The bottle was heated in an oil bath. 450g of tridecafluorooctyl mercaptan and 125g of triethylamine were added. The temperature was raised to 45°C, and 87g of acrylic acid was added dropwise over 2 hours. The temperature was then raised to 55°C, and the reaction was continued at this temperature for 15 hours. A sample was taken for testing: 1.2% mercaptan residue was observed. The temperature was gradually increased, and the triethylamine, unreacted acrylic acid, and mercaptan were distilled off. The light yellow residue in the bottle was tridecafluorooctylthiopropionic acid, with a purity of 94.3% and a weight of 498g, yielding a 93% yield.

[0025] This invention utilizes the reaction of fluorinated alkylthiopropionic acid with hydroxyalkylacrylamide / acrylate under catalytic conditions to prepare acrylates with thioether groups. Through the synergistic effect of the CF bond and the thioether bond, the substance exhibits superior anti-aging properties. The synthesis method of this invention is simple, safe, and conducive to industrial production.

[0026] Polymers prepared using the functional acrylates of this invention as raw materials improve the anti-aging properties of the materials.

[0027] For example: Take 180g of functional acrylate, 7.2g of AEO-9 nonionic surfactant, 3.6g of hexadecyltrimethylammonium bromide cationic surfactant, and 420g of deionized water. Dissolve the above materials in a high-speed disperser at 3000r / min for 30 minutes, then homogenize three times with a high-pressure homogenizer to obtain a white homogeneous liquid. Place the obtained emulsion in a 1000mL four-necked glass bottle, heat in a water bath under a nitrogen atmosphere, add 0.6g of acetic acid and 1.1g of azobisisobutyramidine hydrochloride, and keep the reaction at 60-65℃ for 8 hours to obtain a bluish polymer emulsion. Attached Figure Description

[0028] Figure 1 This is a diagram of the experimental synthesis apparatus of the present invention.

[0029] Figure 2 This is the gas chromatographic spectrum of tridecanoic acid.

[0030] Figure 3 This is the gas chromatography-mass spectrometry (GC-MS) chromatogram of tridecanoic acid. Detailed Implementation

[0031] The technical solution of the present invention will be further explained and illustrated below through specific embodiments.

[0032] Raw material: Tridecylfluorooctylthiopropionic acid, prepared in-house. Preparation method is as follows: A 1000ml four-necked glass bottle was prepared with a magnetic stirrer, thermometer, spiked column, collecting bottle, condenser, and constant-pressure dropping funnel. The bottle was heated in an oil bath. 450g of tridecylfluorooctyl mercaptan and 125g of triethylamine were added to the bottle. The temperature was raised to 45℃, and 87g of acrylic acid was added dropwise over 2 hours. The temperature was then raised to 55℃ and the reaction was continued at this temperature for 15 hours. A sample was taken for testing: 1.2% mercaptan residue was observed. The temperature was gradually increased, and the triethylamine, unreacted acrylic acid, and mercaptan were distilled off. The light yellow residue in the bottle was tridecylfluorooctylthiopropionic acid, with a purity of 94.3% and a weight of 498g, yielding 93%.

[0033] Gas chromatography analysis such as Figure 2 .

[0034] Temperamental mapping ( Figure 3 The analysis is as follows:

[0035]

[0036] ①452.1 is the molecule in question.

[0037]

[0038] ②378.1 (452.1-378.1=74) may be fragment ions that have lost 3 -F and 1 -OH (3*19+17=74).

[0039]

[0040] ③ 119.0 could be 5 -F's and 2 C's (5*19+2*12=119.0).

[0041]

[0042] ④131.0 could be 5 -F and 3 C (5*19+3*12=131.0),

[0043]

[0044] ⑤ 169.0 could be 7 -F and 3 C (7*19+3*12=131.0),

[0045]

[0046] Similarly, nonafluorobutyropropionic acid can be obtained: C4F9-CH2CH2-S-CH2CH2COOH.

[0047] N-Hydroxymethylacrylamide, Aladdin Chemical Reagent;

[0048] N-Hydroxyethylacrylamide, N-Hydroxyethylmethacrylamide, Aladdin Chemical Reagent;

[0049] Hydroxyethyl acrylate, Aladdin Chemical Reagent;

[0050] Hydroxyethyl chloroacrylate, homemade;

[0051] Toluene, cyclohexane, Aladdin chemical reagents;

[0052] Hydroquinone, sulfuric acid, Tianjin Damao Chemical Reagent Factory;

[0053] 4-Methoxyphenol, p-Toluenesulfonic acid, sodium carbonate, Maclean's chemical reagents.

[0054] Example 1:

[0055] 1000ml four-necked glass bottle, equipped with oil bath heating, magnetic stirring, thermometer, spiked glass column, oil-water separator and condenser (e.g.) Figure 1 (As shown).

[0056] 468g of solid tridecafluorooctylthiopropionic acid was added to the flask and heated to melt. Then, 4.25g of p-toluenesulfonic acid and 0.96g of 4-methoxyphenol were added and stirred until homogeneous. Next, 129g of N-hydroxyethylacrylamide and 365g of toluene were added. The temperature was gradually increased to 115℃, at which point an azeotrope of toluene and water began to form. This azeotrope was separated by a barbed column and entered an oil-water separator. The aqueous phase settled to the lower liquid layer, and when a certain amount of toluene accumulated, it was refluxed back into the reaction glass flask.

[0057] Over time, the amount of water produced gradually decreased, and after 11 hours of reaction, no obvious water droplets were produced. Toluene was recovered by negative pressure distillation. Unreacted raw materials and other low-boiling-point substances were then removed under vacuum. The material in the glass bottle was cooled to 80°C, washed once with 5% sodium carbonate solution and once with deionized water, and then dehydrated under vacuum. A yellow viscous product was obtained (molecular formula:

[0058] C6F 13 -CH2CH2-S-CH2CH2COOCH2CH2NHCOCH=CH2), yield 502g, 91.5%.

[0059] Example 2:

[0060] A 1000ml four-necked glass flask is equipped with an oil bath heater, magnetic stirrer, thermometer, spiked glass column, oil-water separator, and condenser. 420g of solid tridecafluorooctylthiopropionic acid is added to the flask and heated to melt. Then, 4g of p-toluenesulfonic acid and 1.1g of 4-methoxyphenol are added and stirred until homogeneous. Next, 120g of N-hydroxyethylacrylamide and 300g of cyclohexane are added. The temperature is gradually raised to 83℃, at which point an azeotrope of cyclohexane and water begins to form. This azeotrope is separated by the spiked column and enters the oil-water separator. The aqueous phase settles to the lower liquid layer, and when a certain amount of cyclohexane accumulates, it is refluxed back into the reaction flask.

[0061] Over time, the amount of water produced gradually decreased, and after 16 hours of reaction, no obvious water droplets were produced. Cyclohexane was recovered by atmospheric distillation. Unreacted raw materials and other low-boiling-point substances were then removed under vacuum. The contents of the glass bottle were cooled to 80°C, washed once with 5% sodium carbonate solution and once with deionized water, and then dehydrated under vacuum. A light yellow viscous product was obtained (molecular formula:

[0062] C6F 13 -CH2CH2-S-CH2CH2COOCH2CH2NHCOCH=CH2), yield 475 grams, 92.3% yield.

[0063] Example 3:

[0064] A 1000ml four-necked glass flask was equipped with an oil bath heater, magnetic stirrer, thermometer, spiked glass column, oil-water separator, and condenser. 420g of solid tridecafluorooctylthiopropionic acid was added to the flask and heated to melt. Then, 3.9g of p-toluenesulfonic acid and 1.1g of 4-methoxyphenol were added and stirred until homogeneous. Next, 101g of N-hydroxymethylacrylamide and 287g of cyclohexane were added. The temperature was gradually raised to 84℃, at which point an azeotrope of cyclohexane and water began to form. This azeotrope was separated by the spiked column and entered the oil-water separator. The aqueous phase settled to the lower liquid layer, and when a certain amount of cyclohexane accumulated, it was refluxed back into the reaction flask.

[0065] Over time, the amount of water produced gradually decreased, and after 17 hours of reaction, no obvious water droplets were produced. Cyclohexane was recovered by atmospheric distillation. Unreacted raw materials and other low-boiling-point substances were then removed under vacuum. The contents of the glass bottle were cooled to 80°C, washed once with 5% sodium carbonate solution and once with deionized water, and then dehydrated under vacuum. A light yellow viscous product was obtained (molecular formula:

[0066] C6F 13 -CH2CH2-S-CH2CH2COOCH2NHCOCH=CH2), yield 432g, yield 87%.

[0067] Examples 4-6:

[0068] The operation method is as described in Examples 1-3.

[0069]

[0070]

[0071] The molecular formulas of the above embodiments are as follows:

[0072] C6F 13 -CH2CH2-S-CH2CH2COOCH2CH2OCOCH=CH2

[0073] C6F 13 -CH2CH2-S-CH2CH2COOCH2CH2OCOCH=CH2

[0074] C6F 13 -CH2CH2-S-CH2CH2COOCH2CH2NHCOCH=CH2

[0075] Examples 7-10:

[0076]

[0077] The molecular formulas of the above embodiments are as follows:

[0078] C6F 13-CH2CH2-S-CH2CH2COOCH2CH2OCOC(CH3)=CH2

[0079] C6F 13 -CH2CH2-S-CH2CH2COOCH2CH2OCOC(Cl)=CH2

[0080] C4F9-CH2CH2-S-CH2CH2COOCH2CH2OCOCH=CH2

[0081] C4F9-CH2CH2-S-CH2CH2COOCH2CH2NHCOC(CH3)=CH2

[0082] Take 180 g of the acrylate synthesized in Example 1, 7.2 g of AEO-9 nonionic surfactant, 3.6 g of hexadecyltrimethylammonium bromide cationic surfactant, and 420 g of deionized water. Dissolve the above materials in a high-speed disperser at 3000 rpm for 30 minutes, then homogenize three times using a high-pressure homogenizer to obtain a white, homogeneous liquid. Place the obtained emulsion in a 1000 mL four-necked glass bottle, heat in a water bath under a nitrogen atmosphere, add 0.6 g of acetic acid and 1.1 g of azobisisobutyramidine hydrochloride, and react at 60–65 °C for 8 hours to obtain a bluish polymer emulsion, experimental sample 1.

[0083] Take the acrylate obtained in Examples 2-10, add 180 grams, keep other auxiliary materials and process conditions unchanged, and obtain experimental samples 2-10 according to the above method.

[0084] Comparative Example 1:

[0085] 250ml four-necked glass bottle, equipped with oil bath heating, magnetic stirring, thermometer, spiked glass column, oil-water separator and condenser (e.g.) Figure 1 (As shown).

[0086] Add 100g of dodecylthiopropionic acid (90%, Maclean), 4.25g of p-toluenesulfonic acid, and 0.96g of 4-methoxyphenol to the flask, stir well, and then add 46g of N-hydroxyethylacrylamide and 95g of toluene. Gradually raise the temperature to 112℃, and an azeotrope of toluene and water begins to form. After separation by a spiked column, the mixture enters an oil-water separator, where the aqueous phase settles to the lower liquid layer. When the toluene accumulates to a certain amount, it is refluxed back into the reaction glass flask.

[0087] Over time, the amount of water produced gradually decreased, and after 14 hours of reaction, no obvious water droplets were produced. Toluene was recovered by negative pressure distillation. Unreacted raw materials and other low-boiling-point substances were then removed under vacuum. The material in the glass bottle was cooled to 80°C, washed once with 5% sodium carbonate solution and once with deionized water, and then dehydrated under vacuum. A yellow viscous product was obtained (molecular formula:

[0088] C 12 H 25 -S-CH2CH2COOCH2CH2NHCOCH=CH2), yield 120.5g, yield 89%, denoted as sample A.

[0089] Comparative Example 2:

[0090] As in Comparative Example 1, replacing N-hydroxyethylacrylamide with hydroxyethyl acrylate yields the same molecular formula:

[0091] C 12 H 25 The yellow product of -S-CH2CH2COOCH2CH2OCOCH=CH2 is denoted as sample B.

[0092] Using octadecyl acrylate (molecular formula: C) 18 H 37 OCOCH=CH2), perfluorohexyl ethyl methacrylate (molecular formula: C6F) 13 CH2CH2OCOC(CH3)=CH2), the molecular formula of perfluoroalkyl ethyl acrylate is:

[0093] C n F 2n+1 CH2CH2OCOCH=CH2 (n≈8.5) (from Aladdin Chemical Reagent Company) and samples A and B obtained from comparative examples were subjected to emulsion polymerization, with other excipients and processes remaining unchanged. Comparative samples 1 to 5 were obtained.

[0094] Take 5 grams of each of the experimental samples 1-10 and comparison samples 1-5 and place them in a 60 mm diameter petri dish, allowing them to level naturally. Place them in an oven and dry at 75 °C for 12 hours and then at 120 °C for 6 hours to obtain translucent thin films.

[0095] The prepared thin-film samples were placed in an aging chamber at a temperature of 90°C, and the yellowing time of the samples was observed. The test data shows that the anti-aging properties of the emulsion polymerization products of independent hydrocarbon acrylates and fluorinated acrylates are weaker than those of the emulsion polymerization products of acrylates containing perfluoroalkyl and sulfur groups of this invention.

[0096] Experimental Sample 1 330 -S- <![CDATA[C6F 13 -]]> Experimental Sample 2 320 -S- <![CDATA[C6F 13 -]]> Experimental Sample 3 290 -S- <![CDATA[C6F 13 -]]> Experimental Sample 4 300 -S- <![CDATA[C6F 13 -]]> Experimental sample 5 325 -S- <![CDATA[C6F 13 -]]> Experimental Sample 6 340 -S- <![CDATA[C6F 13 -]]> Experimental sample 7 330 -S- <![CDATA[C6F 13 -]]> Experimental Sample 8 320 -S- <![CDATA[C6F 13 -]]> Experimental sample 9 285 -S- <![CDATA[C4F9-]]> Experimental sample 10 270 -S- <![CDATA[C4F9-]]> Comparison Sample 1 190 -S- —— Comparison Sample 2 185 -S- —— Comparison Sample 3 150 —— —— Comparison Sample 4 200 —— <![CDATA[C6F 13 -]]> Comparison Sample 5 210 —— <![CDATA[C n F 2n+1 -(n≈8.5)]]>

Claims

1. A functional acrylate, characterized in that... The functional acrylate has the following structural formula: Rf-CH2CH2-S-CH2CH2COOR1XCOCR2=CH2; Where Rf = F(CF2) n -, n=4~6; R1=-(CH2) m -, m=1~3; R2=-H, -CH3, -F or -Cl; X=NH or O.

2. The functional acrylate according to claim 1, characterized in that... The functional acrylate has the following structural formula: Rf-CH2CH2-S-CH2CH2COOR1XCOCR2=CH2; Where Rf = F(CF2) n -, n=6, that is, Rf=-C6F 13 R1 = -(CH2) m -, m=2, i.e. -(CH2CH2)-; R2=-H.

3. A method for preparing the functional acrylate according to claim 1, characterized in that: It is prepared by reacting fluoroalkylthiopropionic acid with N-hydroxyacrylamide or hydroxyalkyl acrylate in the presence of solvent, catalyst and polymerization inhibitor. The structure of the fluorinated alkylthiopropionic acid is: Rf-CH2CH2-S-CH2CH2COOH, Rf=F(CF2). n -, n = 4 to 6; The structure of the N-hydroxyacrylamide or hydroxyalkyl acrylate is: CH2=CR2COXR1OH, R1=-(CH2) m -, m=1~3; R2=-H, -CH3, -F or -Cl; X=NH or O.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the fluorinated alkylthiopropionic acid to N-hydroxyacrylamide or hydroxyalkyl acrylate is 1:1 to 1.

5.

5. The preparation method according to claim 3, characterized in that: The solvent is selected from toluene, n-hexane, and cyclohexane.

6. The preparation method according to claim 3, characterized in that: The catalyst is selected from p-toluenesulfonic acid, sulfuric acid, and sodium bisulfate.

7. The preparation method according to claim 3, characterized in that: The polymerization inhibitor is selected from hydroquinone, 4-methoxyphenol, and 4-hydroxy-TEMPO.

8. The preparation method according to claim 3, characterized in that: In the preparation of functional acrylates, the reaction temperature is 70–150℃ and the reaction time is 8–30 hours.

9. The application of the functional acrylate according to claim 1, characterized in that: Polymers are prepared using the aforementioned functional acrylates as raw materials to improve the anti-aging properties of the materials.

Citation Information

Patent Citations

  • Preparation method of heat-resisting stabilizing agent of bisphenolmonoacryates

    CN101693662B

  • A layered bisphenol acrylate antioxidant and its preparation method

    CN111689853B

  • Fluorine containing photocurable composition

    CN1882618A

  • Surfactant composition, coating composition, and resist composition

    JP2015117327A